2019
DOI: 10.1002/app.47654
|View full text |Cite
|
Sign up to set email alerts
|

Zinc ion conducting blended polymer electrolytes based on room temperature ionic liquid and ceramic filler

Abstract: Zinc ion conducting nanocomposite gel polymer electrolytes (NCGPEs) comprising of poly(vinyl chloride) (PVC)/poly(ethyl methacrylate) (PEMA) blend, zinc triflate [Zn(OTf)2] salt, 1‐ethyl‐3‐methylimidazolium bis(trifluoromethylsulfonyl)imide (EMIMTFSI) ionic liquid (IL) and fumed silica (SiO2) viz. [PVC/PEMA–Zn(OTf)2–EMIMTFSI–SiO2] exhibited the highest ionic conductivity value of 6.71 × 10−4 Scm−1 at room temperature. The ion–filler–polymer interactions and probable conformational changes observed in the struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…35 Also, residual N,Ndimethylformamide (DMF) was also observed to be trapped in gel electrolytes based on poly(vinyl chloride) poly(ethylmethacrylate) blends for Zn 2+ ionic conductivity. 36 Furthermore, residual NMP in poly(vinylidene fluoride-co-hexafluoropropylene)-based gel electrolytes showed an enhanced Zn 2+ ionic conductivity. 37 Nairn et al demonstrated that composite electrolytes of ceramic Li1.3Al0.3Ti1.7(PO4)3 and polyetherurethane:LiCF3SO3 when exposed to DMF, acetonitrile, or water vapors showed enhanced ionic conductivity "beyond simple plasticization of the polymer" by improving the surface contact between the polymer and the ceramic.…”
Section: Conductivity Of Peo:litfsi Films-blockingmentioning
confidence: 98%
“…35 Also, residual N,Ndimethylformamide (DMF) was also observed to be trapped in gel electrolytes based on poly(vinyl chloride) poly(ethylmethacrylate) blends for Zn 2+ ionic conductivity. 36 Furthermore, residual NMP in poly(vinylidene fluoride-co-hexafluoropropylene)-based gel electrolytes showed an enhanced Zn 2+ ionic conductivity. 37 Nairn et al demonstrated that composite electrolytes of ceramic Li1.3Al0.3Ti1.7(PO4)3 and polyetherurethane:LiCF3SO3 when exposed to DMF, acetonitrile, or water vapors showed enhanced ionic conductivity "beyond simple plasticization of the polymer" by improving the surface contact between the polymer and the ceramic.…”
Section: Conductivity Of Peo:litfsi Films-blockingmentioning
confidence: 98%
“…However, for polymer electrolytes, because of the lower ionic transportation and greater zinc dendrite prevention abilities, the development of polymer electrolytes for flexible ZIBs are emphasized on evaluating ionic conductivities and adding additional features. For solid polymer electrolytes, ionic liquids such as [EMIM]BF 4 [ 73 ] and EMIMTFSI [ 138 ] are organic additives improving ionic conductivities from 10 −6 S cm −1 to 10 −3 S cm −1 . Moreover, inorganic additives, such as SiO 2 [ 138 ] and TiO 2 [ 54 ] are also essential materials to expand the free volume for segmental motions.…”
Section: Hybrid Polymer Electrolytesmentioning
confidence: 99%
“…For solid polymer electrolytes, ionic liquids such as [EMIM]BF 4 [ 73 ] and EMIMTFSI [ 138 ] are organic additives improving ionic conductivities from 10 −6 S cm −1 to 10 −3 S cm −1 . Moreover, inorganic additives, such as SiO 2 [ 138 ] and TiO 2 [ 54 ] are also essential materials to expand the free volume for segmental motions. For hydrogel electrolytes, anti‐freezing ability, thermoresponsive ability and high tensile strength are achieved with various additives.…”
Section: Hybrid Polymer Electrolytesmentioning
confidence: 99%
“…Prasanna et al [334] used a nanocomposite gel polymer electrolytes (NCGPEs) comprising of salt, 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (EMIMTFSI) ionic liquid (IL) and fumed silica (PVC/PEMA poly(ethyl methacrylate) blend, zinc triflate Zn(Tf) 2 , SiO 2 as thickening agent. Maximum conductivity for this gel was achieved for 3 wt.% SiO 2 (6.71•10 −4 Scm −1 ).…”
Section: Others Polymer Electrolytesmentioning
confidence: 99%